2004
DOI: 10.1038/sj.ejhg.5201335
|View full text |Cite
|
Sign up to set email alerts
|

Possible role of USP26 in patients with severely impaired spermatogenesis

Abstract: The ubiquitin-specific protease 26 (USP26) gene is an X-linked gene specifically expressed in testis tissue. This gene is therefore a potential infertility gene. In order to analyse its possible involvement in spermatogenesis and infertility, 42 patients with Sertoli cell-only syndrome were analysed for mutations in this gene. We found four patients with exactly the same three changes of the nucleotide and therefore also amino acid sequence. These patients showed 370-371insACA, 494T4C and 1423C4T causing T123-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
85
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 8 publications
6
85
0
3
Order By: Relevance
“…Recently, Ribarski et al, [110], reported high frequency (4.7 %) of 1090C>T mutations in infertile patients. Stouffs et al, [111] reported the presence of some mutations in USP26 gene such as 370-371insACA, 494 T>C and 1423C>T in patients (7.2 %) with SCOS.…”
Section: The Usp26 Gene Mutationsmentioning
confidence: 99%
“…Recently, Ribarski et al, [110], reported high frequency (4.7 %) of 1090C>T mutations in infertile patients. Stouffs et al, [111] reported the presence of some mutations in USP26 gene such as 370-371insACA, 494 T>C and 1423C>T in patients (7.2 %) with SCOS.…”
Section: The Usp26 Gene Mutationsmentioning
confidence: 99%
“…In several genetic studies, two X-linked germ cellspecific genes (TAF7L and USP26) were screened for mutations in infertile men (Paduch et al 2005, Stouffs et al 2005, 2006b. Mutation screening of TAF7L in 25 men with non-obstructive azoospermia did not reveal mutations that are associated with infertility (Stouffs et al 2006b).…”
Section: Implications Of X-linked Meiosis Factorsmentioning
confidence: 99%
“…Mutation screening of TAF7L in 25 men with non-obstructive azoospermia did not reveal mutations that are associated with infertility (Stouffs et al 2006b). Two studies indicated that a haplotype in USP26 (371insACA, 494T9C and 1423C9T) might be a risk factor for male infertility (Paduch et al 2005, Stouffs et al 2005. In contrast, other studies showed that this USP26 haplotype is a polymorphism in non-Caucasian populations (Ravel et al 2006, Stouffs et al 2006a.…”
Section: Implications Of X-linked Meiosis Factorsmentioning
confidence: 99%
“…In addition to Y chromosome microdeletion and mutation of autosome genes, X chromosomes are also closely related to male fertility; however, the underlying molecular mechanisms are still unknown [3,5]. There has been an intensive search in such genes located on the X chromosome as men are hemizygous for this chromosome [6,7]. Nishimune et al [8] observed many genes on the X chromosome that are related to male infertility.…”
Section: Introductionmentioning
confidence: 99%
“…Its mouse homolog was found to be only expressed in spermatogonia [9]. Given the importance of DUBs, the testis-specific expression of USP26, its putative role in regulation of the spermatogenesis, and its location on the X chromosome, which limits the gene to a single allele in an individual, this gene have been considered as a novel and attractive candidate gene for the study of male infertility [6,8,9].…”
Section: Introductionmentioning
confidence: 99%